AKUNTABILITAS PENGELOLAAN KEUANGAN PARTAI POLITIK LOKAL ACEH - Ikhwan Rahmatika Latif; Ikhsan; Fadli Afriandi; Akmal Saputra; Yeni Sri Lestari (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2022)
The formation of local political parties in Aceh is an example of an asymmetrical political policy being carried out by the Indonesian government in relation to Aceh's status as a region with a special autonomy. In that situation, the concept of accountability inside national political parties needs to be discussed as well in order to figure out how local party accountability is applied in Aceh. When it comes to the presentation of data connected to outcomes that have been produced by earlier researchers, this study makes use of the documentation approach. According to the conclusions of this study of Aceh's local political parties, the level of accountability and transparency that has been maintained by Aceh's local political parties in general has been pretty satisfactory. Even though in general terms the provisions are still not as good as they should be, the Aceh Party has become the most complete in carrying out its principle of financial accountability. This is the case despite the fact that the Aceh Party has become the most comprehensive.